Predominant theoretical perspectives on China's approach to IR as a discipline: between autonomy and integration - Aristegui, Carlos Monge [UNESP] (Pontificia Universidade Catolica de Minas Gerais, 2021)
The rise of the People's Republic of China (PRC) in the international system has effects and consequences in all areas of study, including International Relations (IR) as a discipline. After an initial period of isolation, after the Revolution led by Mao Zedong, in 1949, the process of Reform and Opening, led by Deng Xiaoping, from 1978, made the Chinese academy reconnect with a field of studies with predominance of theoretical frameworks from the Anglo-Saxon world. This supposed that the Chinese researchers had a stage of uncritical absorption of this knowledge, classified as learning and copying, in which the same debates that have taken place in the West were incorporated, without further questioning. However, in the second half of the 1980s, voices emerged that raised question's for a Chinese perspective in addressing these issues. Thus, its own literature developped toward this topic, and in the 2000s two integrative views appear and are consolidated: those of Yan Xuetong and Qin Yaqing, who propose, with different emphases and intentions, to link the Western Theory of IR with classical Chinese thinking. Another author, Zhao Tingyang, claims the Tianxia (All-under-Heaven), worldview of the pre-Qin era (2100 to 221 BC), as a possible alternative to the Westphalian paradigm. The following work analyzes this phenomenon, as well as the new epistemological approaches that assuming this challenge implies.
Perspectivas teóricas predominantes na abordagem da China em relacao as RI como disciplina: entre autonomia e integracao
Keywords: Chinese School of International Relations; Epistemological approaches; RI with Chinese characteristics; Theory of International Relations; Tianxia